A Ten-Month Infant with Bladder Botryoid Sarcoma: Sarcoma Botryoides of Bladder - Arun Babu, Thirunavukkarasu; Balakrishnan, Padmapriya; Sharmila, Vijayan (Journal of Pediatric Nephrology, 2021)
Bladder tumors resulting in voiding difficulty in a child are rarely encountered in clinical practice. There are various investigations that help with preoperative diagnosis of bladder tumors and a systematic approach is needed to draw an early diagnosis. We report a case of the botryoid variant of rhabdomyosarcoma of the bladder in an infant that presented with complaints of a lower abdominal mass, poor urinary stream for three months and hematuria for one month.